-1/3+2t=-1/3(9t-2)

Simple and best practice solution for -1/3+2t=-1/3(9t-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1/3+2t=-1/3(9t-2) equation:


t in (-oo:+oo)

2*t-1/3 = (-1/3)*(9*t-2) // - (-1/3)*(9*t-2)

2*t-((-1/3)*(9*t-2))-1/3 = 0

(1/3)*(9*t-2)+2*t-1/3 = 0

1/3*(9*t-2)+2*t-1/3 = 0

(1/3*3*(9*t-2))/3+(2*3*t)/3-1/3 = 0

1/3*3*(9*t-2)+2*3*t-1 = 0

15*t-2-1 = 0

15*t-3 = 0

(15*t-3)/3 = 0

(15*t-3)/3 = 0 // * 3

15*t-3 = 0

15*t-3 = 0 // + 3

15*t = 3 // : 15

t = 3/15

t = 1/5

t = 1/5

See similar equations:

| D=tres | | y^2-100=4y | | 10y-4y-8=20 | | (u-4)^2/3 | | 4k=60+6k | | 9/5(k-273.15) | | 3-2/6b=1/3b-7 | | k+10/k=4/6 | | 10(x^2-21x+75)=0 | | 5x+2(5x-2)=176 | | 3(2x-2)=4(x+4) | | 8x+10-2x+36=4x+15+8x-28 | | n+1=13-2n+n | | 10y-4-8=20 | | 3(3.99)+1b-0.11=5b | | (2x-3)(2x+3)=55 | | x^2-21x+75=0 | | 5y-4=8+y | | 3x-2=7x+6 | | -4+4/5x=6 | | -5=9+c-4 | | 5x-3+4x-24=3x+2+4x-9 | | -2(6+4b)=-6b | | 10y-4g-8=20 | | r/10+1.1=0.3 | | 2n+3.5=6.7 | | W^2+7=w^3+9 | | (A^-3b6-4/a^7b^3)(a^3b^4/a^-3b^-3)^2 | | 5x-3(x-5)=15 | | 2p-2=14+6p | | 6(r+7)=35+5r | | 3x=56+7(9)y |

Equations solver categories